2019
DOI: 10.1016/j.psychsport.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Teammate influences on the eating attitudes and behaviours of athletes: A systematic review

Abstract: Background: It has been well documented that athletes are at an increased risk of developing disordered eating attitudes and behaviours. Over the last two decades, researchers have focused their attention on how teammates may influence athletes' eating attitudes and behaviours. Objective: To systematically review the literature relating to teammate influences on athletes' eating attitudes and behaviours. Method: A systematic literature search of the SPORTDiscus, PsycINFO and MEDLINE databases was conducted. Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 75 publications
(109 reference statements)
6
23
1
Order By: Relevance
“…For example, through the modelling of teammates’ disordered eating (Arthur‐Cameselle, Sossin, & Quatromoni, ; Engel et al, ) or perceiving a pressure from teammates to lose weight/change shape (Petrie, Greenleaf, Carter, & Reel, ; Petrie, Greenleaf, Reel, & Carter, ). In line with this, a large‐scale cross‐sectional study (Scott, Haycraft, & Plateau, ) that assessed the importance of multiple teammate influence mechanisms revealed that for both males and females, the best teammate influence predictors of elevated eating and exercise psychopathology were a perceived pressure from teammates to lose weight/change shape and the modelling of teammates’ bingeing and purging behaviors. Conversely, the best predictor of reduced eating and exercise psychopathology was having supportive teammate friendships.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…For example, through the modelling of teammates’ disordered eating (Arthur‐Cameselle, Sossin, & Quatromoni, ; Engel et al, ) or perceiving a pressure from teammates to lose weight/change shape (Petrie, Greenleaf, Carter, & Reel, ; Petrie, Greenleaf, Reel, & Carter, ). In line with this, a large‐scale cross‐sectional study (Scott, Haycraft, & Plateau, ) that assessed the importance of multiple teammate influence mechanisms revealed that for both males and females, the best teammate influence predictors of elevated eating and exercise psychopathology were a perceived pressure from teammates to lose weight/change shape and the modelling of teammates’ bingeing and purging behaviors. Conversely, the best predictor of reduced eating and exercise psychopathology was having supportive teammate friendships.…”
Section: Introductionmentioning
confidence: 79%
“…Global self‐esteem has been widely assessed using the RSES in athlete populations (e.g., Engel et al, ; Scott et al, ). Athletes responded to 10 items using a 4‐point Likert scale ranging from 1 (“strongly disagree”) to 4 (“strongly agree”).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations